The cationic cell‐penetrating KT2 peptide promotes cell membrane defects and apoptosis with autophagy inhibition in human HCT 116 colon cancer cells - Maraming, Pornsuda; Klaynongsruang, Sompong; Boonsiri, Patcharee; Peng, Shu‐Fen; Daduang, Sakda; Leelayuwat, Chanvit; Pientong, Chamsai; Chung, Jing‐Gung; Daduang, Jureerut (Journal of cellular physiology, 2019)
The anticancer activity of cationic antimicrobial peptides (AMPs) has become more interesting because some AMPs have selective recognition against cancer cells. However, their antitumor properties and underlying mechanisms in cancer cells have not been clearly understood. In this study, we evaluated the effects of KT2 (lysine/tryptophan‐rich AMP) on the cellular uptake and internalization mechanism, cell viability, surface charge of the cell membrane, membrane integrity, apoptotic cell death, and autophagy in human HCT 116 colon cancer cells. We found that KT2 interacted with the cell membrane of HCT 116 cells and was internalized into HCT 116 cells via clathrin‐mediated and caveolae‐mediated endocytosis mechanisms. The interaction of KT2 with cells caused cell membrane structure change, elevated membrane permeability, and KT2 also affected the lipid component. The results of atomic force microscopy showed cellular membrane defects of KT2‐treated cells. The internalized KT2 induced nuclear condensation and apoptotic cell death. It elevated the apoptotic factor levels including those of cytochrome c and apoptosis‐inducing factor. Furthermore, KT2 inhibited autophagy by the suppression of autophagy‐related 5, autophagy‐related 7, autophagy‐related 16 like 1, and Beclin‐1 proteins. In conclusion, these results revealed the cytotoxicity of cationic KT2 against HCT 116 cells and may help to clarify the interactions between cationic AMPs and cancer cells. Our findings showed that KT2 interacts with the plasma membrane and is then internalized into cells. Moreover, the KT2 peptide increases membrane permeability and induces cytotoxicity against cancer cells through DNA condensation, the increase of apoptotic factor protein levels, and autophagy suppression.